Host range conferred by the virulence-specifying plasmid of Agrobacterium tumefaciens. - Loper, J E (1979)
The host range of Agrobacterium tumefaciens 1D1109, known to induce crown gall only on grapevine (Vitis spp.), was extended to include many plant species by transferring a tumor-inducing plasmid (pTi) from strain 1D1, a broad-host-range pathogen. The pTi plasmid was mobilized by the conjugative plasmid pRK2, which was inserted into 1D1 by mating with Escherichia coli J53(pRK2). The resulting transconjugants were screened for their ability to induce crown gall tumors on hosts other than grapevine by inoculation into sunflower. Transconjugants that were virulent on sunflower were then tested on 36 different host plants and compared with host-limited strain 1D1109 and the donor strain. Two transconjugants induced tumors on the same 28 plant species as those of the original plasmid donor 1D1(pRK2) (pTi). These results show that pRK2 promoted transfer of the pTi plasmid and suggest that the pTi plasmid rather than the A. tumefaciens chromosome determined the host range of the pathogen. Insertion of pRK2 alone did not extend the host range of strain 1D1109. Insertion of pS-a into A. tumefaciens 1D1 by mating with E. coli J53-1 (pS-a) resulted in the concomitant loss of pTi and virulence. There appears to be incompatibility between pTi and pS-a.